(untitled) (Research, Society and Development, 2024)
Infertility is a condition of the male or female reproductive system, characterized by the inability to conceive after at least 12 months of regular attempts. This issue affects many people throughout their lives, impacting approximately 17.5% of the adult population. This literature review aims to investigate the relationship between nutrition and fertility, highlighting the positive and negative effects that diet can have on reproductive health. Additionally, it seeks to identify the most important nutrients for maintaining fertility at ideal levels, especially regarding oocyte quality, thus promoting conception. For data collection, publications in Portuguese and English from the past six years were consulted in major databases, such as Google Scholar, PubMed, Research, Society and Development, and SciELO. After analyzing the literature, it was observed that nutrition plays a crucial role in female fertility. Studies indicate that a balanced diet, rich in micronutrients with antioxidant properties and meeting daily energy needs, can help combat infertility and improve oogenesis. In addition to diet, it is essential to consider the importance of an active lifestyle and maintaining adequate weight control. Socioeconomic, cultural, and geographical factors can also exert positive or negative influence on the success of conception.